The role of measurement, analysis and knowledge management criterion in MBNQA model to manage institutions of higher education - Ismail, Rosli; Azmi Murad, Masrah Azrifah; A. Jabar, Marzanah; Haizan Nor, Rozi Nor (American-Eurasian Network for Scientific Information, 2015)
The purpose of this research is to empirically test the role of measurement,analysis and knowledge management criterion on Malcolm Baldrige National Quality Award (MBNQA)criteria model for higher education institutions(HEIs). The paper identifies five (5) causal hypotheses from literatures that are related to the measurement, analysis and knowledge management criterion. Structural equation model(SEM)is used to analyse the empirical data that were collected from 118 Malaysian HEIs. The results indicate that there are three(3) significant relations and two (2) insignificant relations within the model. Measurement,analysis and knowledge management have causal positive effect on strategic planning and student,stakeholder and market focus.In addition, leadershiph as causal positive effecton measurement,analysis and knowledge management.However,measurement,analysis and knowledge management do not have causal positive effecton faculty and staff focus and process management. The comprehensiveness of these relationships provides a guide to implement, develop,assess and improve higher education institutions.